Solve the following equations:
3x + 2y = 0
2x + 3y = 0
Answers
Answered by
1
3x+2y = 0 -----eq.1
2x+3y = 0 -----eq.2
form eq.1
x = -2y/3 -----eq.3
now.. substitute the value of x in eq.2
=> 2(-2y/3+3y) = 0
=> -4y/3+3y = 0
=> -4y+9y = 0
=> 5y = 0
=> y = 0
now substitute the value of y in eq.3
=> x = -2×0/3
=> x = 0
so value of x = 0 and y = 0
Answered by
1
Answer:
Step-by-step explanation:
Given equations are
3x+2y=0-----(1)
2x+3y=0----(2)
adding (1)&(2)
=>5x+5y=0
=>5(x+y)=0
=>x+y=0.....(3)
subtracting (2) from (1)
=>3x-2x+2y-3y=0
=>x-y=0-----(4)
From(3)&(4)
x+y=0
x-y=0
----------
2x+0=0
=>2x=0
=>x=0/2
Therefore ,x=0
and from(3)
0+y=0
=>y=0
The solution is (0,0)
Similar questions